I am your trans patient. (30th June 2017) - Lewis, Emma-Ben; Vincent, Ben; Brett, Alex; Gibson, Sarah; Walsh, Reubs J
Abstract : For the first time we are publishing a What Your Patient is Thinking article by a group of people. These transgender authors share their experiences of healthcare and the important messages they would like doctors to know